Study The Properties of Structural And Optical of Cadmium Oxide Films Prepared In A Thermal Evaporation In A Vacuum - Maki, Samir A.; AbdulRidha, Zaynab S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In   this  research  ,  the  structural   and  optical   properties   of  pure of cadmium  oxide, pure (CdO) were studided thin films in a thermal evaporation in a vacuum depositing metal cadmium pure rules of the glass at room temperature (300K) and thickness (300 Â± 20nm) and the time of deposition (1.25sec) was oxidation of thin films cadmium (Cd) record temperature (673k) for a period of one hour to the presence of air optical energy gap for direct electronic transitions were calculated (permitted) as a function of absorption coefficient and permeability and reversibility by recording the spectrum absorbance and permeability of the membrane the record within the wavelengths (300-1100nm).